A rational approach towards selective ethylene oligomerization via PNP-ligand design with an N-triptycene functionality. Issue 72 (19th August 2022) - Barman, Samir; Jaseer, E. A.; Garcia, Nestor; Elanany, Mohamed; Khawaji, Motaz; Xu, Wei; Lin, Sibo; Alasiri, Hassan; Akhtar, Muhammad Naseem; Theravalappil, Rajesh
Abstract : Novel PNP ligands bearing an N -triptycene backbone were developed and evaluated for selective ethylene oligomerization. Abstract : Novel PNP ligands bearing an N -triptycene backbone were developed and evaluated for selective ethylene oligomerization. Upon activation with MMAO-3A, the pre-catalyst mixture containing Cr(acac)3 /ligand efficiently promotes ethylene tetramerization with remarkably high productivities (up to 1733 kg gCr −1 h −1 ) and C8 olefin selectivities (up to 74.1 wt%). More importantly, ligands with a PNP moiety connecting at the 1- or 1, 4-position of the triptycene molecule could achieve exceptionally high alpha (1-C6 + 1-C8 ) selectivities, exceeding 90 wt%, as a result of high 1-C6 purity (>90 wt%) in the C6 fraction. Based on comparative catalytic studies employing various PNP ligands with or without an N -triptycene backbone, we illustrate the fact that a rational design of PNP ligands with an optimum degree of steric profile around the N-center could provide C6 cyclics controlled highly α-selective ethylene oligomerization.